2019
DOI: 10.3390/jcm8081238
|View full text |Cite
|
Sign up to set email alerts
|

Association between Secondhand Smoke Exposure and Hypertension in 106,268 Korean Self-Reported Never-Smokers Verified by Cotinine

Abstract: : No study has reported the relationship between secondhand smoke (SHS) exposure and hypertension in self-reported never-smokers verified by nicotine metabolite. The aim of this study is to determine the relationship between SHS exposure and hypertension in self-reported and cotinine-verified never-smokers. A total of 106,268 self-reported never-smokers, verified as nonsmokers by urinary cotinine, who participated in Kangbuk Samsung Cohort study (KSCS) between 2012 and 2016 were included. Cotinine-verified non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…In our report, we found PSE increased odds of hypertension which is in tandem with similar reports on the contribution of PSE to hypertension [ 24 28 ] and cardiovascular events [ 13 , 20 , 25 , 29 , 30 ]. According to similar reports from other populations, PSE independently increased the risk of hypertension by 11% in a Japanese population [ 24 ], 16% in among Korea adults [ 26 ] and 38% among Chinese women [ 27 ]. Similarly, PSE accounted for about 379,000 ischaemic heart disease-related mortality among adults worldwide in 2004 [ 29 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our report, we found PSE increased odds of hypertension which is in tandem with similar reports on the contribution of PSE to hypertension [ 24 28 ] and cardiovascular events [ 13 , 20 , 25 , 29 , 30 ]. According to similar reports from other populations, PSE independently increased the risk of hypertension by 11% in a Japanese population [ 24 ], 16% in among Korea adults [ 26 ] and 38% among Chinese women [ 27 ]. Similarly, PSE accounted for about 379,000 ischaemic heart disease-related mortality among adults worldwide in 2004 [ 29 ].…”
Section: Discussionmentioning
confidence: 87%
“…For example, a recent report by Xu and colleagues [ 44 ] found PSE significantly increased the risk of AAC among women but not among men in China. However, Kim et al [ 26 ] and Tamura et al [ 24 ] in two separate studies from South Korea and Japan respectively found PSE increased the odds of hypertension independent of sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies which assessed the association between smoking and hypertension have shown inconsistent results [ 4 , 13 , 31 33 ]. However, a recent cross-sectional study which assessed the association between SHS exposure and hypertension in Korean adults has shown that SHS exposure is associated with increased odds for hypertension [ 34 ]. The pathophysiology behind this association is mainly nicotine-mediated sympathetic activation, endothelial dysfunction, hypercoagulation, and increased arterial stiffness [ 31 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the self‐reported questionnaires, SHS smoke exposure was defined as current exposure to passive smoke indoors at home or the workplace. Daily time, weekly frequency, and total duration of SHS exposure were collected 28 …”
Section: Methodsmentioning
confidence: 99%